Dynamics of fish catch results from handline fishing gear and sustainable solutions for tuna fisheries in a rumpon area - Soghirun, Muh.; Rumpa, Arham; Kasim, Nurdin; Ohorella, Rafi; Pontoh, Peggy; Baroqi, A. Riza; Satria Timur , Putra Satria Timur; Runtukahu, Muh. Ikhsan Zulfatan; Novita Ayu Wulandari (Universitas Sam Ratulangi, 2024)
Rumpon, as a fish-aggregating device, has long been used by tuna handline fishermen in Bone Bay, South Sulawesi Province, Indonesia. Information on the characteristics of tuna handline fishing in the area is very limited and is very much needed as study material for tuna fishing strategies and fisheries policies. This research aims to understand the results of handline catches and sustainable solutions for tuna fisheries in rumpon areas. The data used is the result of observations using 19 ships based at PPI Lonrae and data collection for 5 years (2018-2022). The results show that the composition of the main catch is dominated by yellowfin tuna (Thunnus albacares), bigeye tuna (Thunnus obesus), and skipjack tuna (Katsuwonus pelamis). In general, the size of fish that are not suitable for catching for the yellowfin tuna, bigeye tuna, and skipjack tuna, consecutively, is 54.0%, 45.1%, and 31.9%. This finding further clarifies that the percentage of tuna and skipjack tuna that are not suitable for catching is still very large. Continuous and large-scale fishing of juvenile tuna could cause fish resources to continue to decline in the future. Technically, what fishermen need to understand is, in addition to the strategy of lowering fishing gear deeper, the time of fishing and the type of bait used.